ANALISIS PENGENDALIAN PENYALAHGUNAAN AKAD WAKALAH PADA PRODUK PEMBIAYAAN MURABAHAH DI BMT SE-KABUPATEN JEPARA - MAHMUDATUS SA'DIYAH; MOCH AMINNUDIN (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2019)
This study discusses to study the practices, strengths and weaknesses and solutions that support the wakalah contract on murabaha financing products in BMTs in Jepara Regency. The type of this research is field research by obtaining qualitative. Data collection by interview, observation and documentation. Data reduction analysis techniques, data display and drawing conclusions / verification. The results showed that the practice of wakalah on murabaha financing products in BMT in Jepara Regency was BMT and the agreement to negotiate using a wakalah agreement and the transfer of funds after discussing a two-sided agreement, then BMT provided the hands asking for buying and selling letters and letters in question, then to buy goods to the supplier then send the goods to the buyer to BMT, then send to the buyer at BMT in accordance with the initial agreement. The advantage of wakalah practice on murabaha financing products in BMT is to build high trust between BMT and funds to translate in financing. The disadvantage is that most that do not deserve to understand BMT financing products, lack of openness about the business conditions to be funded, need deviations from the agreed agreement. The fix is to stick to the principle 5C and consider three important aspects of financing, which are safe, efficient, and profitable